Kepemimpinan Transformasional, Motivasi Kerja dan Keterlibatan Kerja Dalam Meningkatkan Kinerja Karyawan Hotel Radjendra Resort and Resto Caringin Bogor - Mulyani, Rema (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to see how transformational leadership, work motivation, and work involvement contribute significantly to improving employee performance. The object of the study was employees at the Radjendra Resort and Resto Hotel Caringin Bogor, with a quantitative approach and associative research design. The sample consisted of 52 respondents determined through random sampling techniques using the Slovin formula from a total population of 102 employees. After the data was collected through a Likert-scale questionnaire, multiple linear regression was implemented to analyze it. The findings prove that the three independent variables studied provide a significant contribution to improving employee performance, both separately and simultaneously. This confirms that visionary leadership, strong work motivation, and employee emotional and cognitive involvement collectively create a productive work environment. The uniqueness of this study lies in the simultaneous testing of the three variables in the context of the local hospitality industry, which is still rarely studied. Hopefully, these findings will help make strategic policies for HR management in the hospitality sector.